SDGs-Based Environmental Education at TPQ At Thariq, Bone Bolango Regency - Wunarlan, Irwan; Botutihe, Muhamad Rifki (Edumedia Solution, 2025)
This community engagement activity aimed to educate children at TPQ At Thariq, Bone Bolango Regency, about the importance of environmental preservation through an approach grounded in the values of the Sustainable Development Goals (SDGs) and aligned with Islamic teachings. The activity was held on Thursday, May 1, 2025, and attended by 17 students. The materials were delivered interactively using storytelling, light discussions, and simple visual media appropriate for children's comprehension levels. The community faced the challenge of limited environmental awareness among young learners. The implemented solution was a contextual and value-based education method that bridges environmental knowledge with religious values. The outcome of the activity revealed high enthusiasm among the participants, who successfully understood key messages such as water conservation, cleanliness, and love for living beings. This context-based approach proved effective in fostering early environmental awareness. It is expected that this initiative may serve as an inspirational model for other TPQs in promoting environmental education.